Nivel de conocimiento y hábitos en salud oral de los adolescentes de la Institución Educativa Simón Bolívar sede central (2024)
To carry out this work, it began with a survey to identify the level of knowledge and habits presented by the population under study. On the other hand, information was provided in a didactic manner through educational talks, board games, memory activities and didactic questions. After the training, a second survey was conducted to evaluate the level of knowledge and habits, in order to reinforce and expand oral health knowledge.